Perpustakaan Baitul Hikmah, Tonggak Kebangkitan Intelektual Muslim - Aris Nurohman (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
The Baitul Hikmah Library was recorded as a library owned by Muslims, which was established during the Abbasid Caliphate which was considered the first largest library to influence Muslim civilization in the field of science. The climax occurred during the caliph al-Ma'mun. Al Ma'mun is able to develop the Baitul Hikmah library with good management, and maximum one of them is through large financial support for research, paying professional librarians, paying for translation and even collaborating with experts from various fields regardless of religious background. As a result, Baitul Wisdom becomes a reference source of important information in various fields, ranging from the social, medical, mathematical, physical and philosophical fields. This is very interesting to be used as the knowledge of library managers at the moment, as well as being an important lesson material about the role of libraries in the development of intelligence and human civilization.